Analysis Of Company Performance Through Financial Aspect And Innovation Capacity At Super Afifah Palu Tofu Factory - Dinno Wahyudhi Purba; Muhammad Din; Jurana Jurana (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2020)
This study aims to analyze the performance of the Tofu Super Afifah Palu Company based on the Financial Aspects and Innovation Capability. This study uses primary and secondary data, with data collection techniques through observation, interviews and documentation. The results of this study indicate that the Company's financial liquidity ratio can be ascertained to be very liquid and is included in the very healthy criteria (94.4% in 2018 and 172.22% in 2019 for the current ratio while for the quick ratio it is 66.40% in 2018 and 127.78% in 2019). Furthermore, the results of the solvency ratio analysis also increased from 2018 to 2019. Both in terms of the Debt to Asset Ratio and the Debt Equity Ratio. However, despite experiencing an increase in the Debt Equity Ratio, the company must pay attention and maximize it again so that in the future it can get an assessment or be included in the healthy criteria. Meanwhile, the company's profitability ratios get very healthy criteria, it can be seen from the results of the ratio calculations which show positive performance from year to year. Meanwhile, the results of the analysis of the aspects of the company's innovation capability were carried out quite well, especially the factors of technology use, interaction with outsiders, new product development and production and operation capabilities that impact on company performance. However, the company is expected to maximize the performance of human resources, marketing capabilities, as well as aspects of research and development